1998
DOI: 10.1074/jbc.273.31.19625
|View full text |Cite
|
Sign up to set email alerts
|

Cellubrevin-targeted Fluorescence Uncovers Heterogeneity in the Recycling Endosomes

Abstract: The pH and trafficking of recycling endosomes have previously been studied using transferrin. We have used another approach, one in which the vesicle transport protein cellubrevin was appended with a luminal IgG epitope to allow targeting of fluorescein-5-isothiocyanate (FITC)-labeled anti-IgG F(ab) antibodies to the recycling endosomes in living cells. FITC-F(ab) was specifically internalized by COS cells transfected with cellubrevin-Ig, which at steady state accumulated in a pericentriolar region similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 40 publications
9
57
0
Order By: Relevance
“…In addition, the partial colocalization of hOAT1 with transferrin and EEA1 could also arise from other possibilities. It has been shown that recycling endosomes are heterogeneous in their biochemical compositions, ion transport properties, and pH values (51). Therefore, it may be possible that some of hOAT1 resides in a different subpopulation of recycling endosomes from that enriched in transferrin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the partial colocalization of hOAT1 with transferrin and EEA1 could also arise from other possibilities. It has been shown that recycling endosomes are heterogeneous in their biochemical compositions, ion transport properties, and pH values (51). Therefore, it may be possible that some of hOAT1 resides in a different subpopulation of recycling endosomes from that enriched in transferrin.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we observed a trend toward increased DAT surface expression following bafilomycin treatment, suggesting that early endocytic trafficking of DAT and TfR are mechanistically distinct. DAT may reside in a subpopulation of early endosomes that is relatively insensitive to bafilomycin and/or pH changes such as reported for cellubrevin (52). Alternatively, DAT may be intrinsically less dependent upon pH for endosomal sorting.…”
Section: Discussionmentioning
confidence: 99%
“…29,77 Currently, immunoisolation studies are also in progress in an attempt to understand the dynamic regulation of recycling, transcytosis, and the caveolin cycle. However, in view of the complexity of the recycling endosomal compartment it is presumable that the physical separation of the 3 functional subcompartments from RRC will be complicated, 37,45,78 even questionable, considering the intricacy of tubulo-network membrane structures and the molecular mix up in single clathrin-coated pits or caveolae plasma membrane microdomains.…”
Section: Is There a Restricted Location For The Rrc In The Hepatocyte?mentioning
confidence: 99%